2017
DOI: 10.1094/cchem-06-17-0125-r
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Fingerprint of Sicilian Modern Cultivars and Durum Wheat Landraces: A Tool to Assess Biodiversity

Abstract: Durum wheat landraces have been recognized to have different contents in health‐promoting phytochemicals. These health benefits have been mainly attributed to the presence of phenolic acids and flavonoids existing in this matrix both as soluble free compounds and insoluble bound forms. Sicily is one of the few areas of Southern Europe where it is still possible to find landraces of durum wheat, no longer cropped because of the commercial spread of new high‐yielding varieties. This study aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…× cornutum IPT211 and IPT214. The ability to identify and characterize local landraces by phenolic profile has been reported previously in different species, cultivars (Riggi et al, 2013; Lo Bianco et al, 2017), and local landraces of A. cepa (Riggi et al, 2013). In our study, the phenolic profile proved to be a powerful tool to discriminate among local shallot accession groups, especially with inclusion of minor phenolic compounds.…”
Section: Discussionmentioning
confidence: 66%
“…× cornutum IPT211 and IPT214. The ability to identify and characterize local landraces by phenolic profile has been reported previously in different species, cultivars (Riggi et al, 2013; Lo Bianco et al, 2017), and local landraces of A. cepa (Riggi et al, 2013). In our study, the phenolic profile proved to be a powerful tool to discriminate among local shallot accession groups, especially with inclusion of minor phenolic compounds.…”
Section: Discussionmentioning
confidence: 66%
“…Nowadays attention is given to the cereals nutritional values and health effects and the terms “ancient grains”, “historical varieties”, “modern varieties” have become common in the scientific community and among consumers, covering a broad subject area, including the identification of varieties. Growing consumer interest in healthy food production has triggered interest in the phytochemical content of ancient and modern durum wheat varieties [10], and this trend led to the rediscovery and re-utilization of durum wheat landraces, including those in Sicily [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to Lo Bianco et al [11], free phenolics were recovered by applying the method proposed by Dinelli et al [14] with few changes. In brief, 1 g of whole wheat flour was mixed under vigorous stirring for 10 min with 20 mL of an acidic aqueous methanol solution (80% methanol, 19% water, 1% formic acid).…”
Section: Extraction Of Free and Bound Phenolic Compoundsmentioning
confidence: 99%
“…According to Lo Bianco et al [11], three hydroxycinnamic acids were identified in wheat grains: caffeic acid (peak 4), ferulic acid (peak 10) and another member of this class (peak 1) for which unfortunately the MS spectrum was not determined. Vanillic acid (peak 3) was identified for its diagnostic UV-VIS and mass spectrum; the assignment was confirmed with co-injection with the corresponding standard.…”
Section: Phenolic Profile In Wheat Landracesmentioning
confidence: 99%
See 1 more Smart Citation